PENGARUH LAMA PENGGUNAAN KONTRASEPSI DMPA (DEPOMEDROXI PROGESTERON ASETAT) TERHADAP PENURUNAN LIBIDO PADA WANITA USIA SUBUR DI BPM LUKLUATUN MUBRIKOH S.ST - lailiyah, Siti rochimatul (NHM PRESS, 2085)
Decrease in libido is often found in injection KB users. Seen from the preliminarystudy, there were 6 people (60%) who experienced a decrease in libido. Purpose of the studyAnalyze the effect of long-term DMPA contraception use on decreasing libido in women ofchildbearing age.The design of this study used analytical survey with a cross sectional approach. Theindependent variable is the duration of use of DMPA contraseption. The dependent variableis libido, the population used by all women of childbearing age acceptors who use DMPAcontraception from the beginning until now, with a sample of 50 respondents. The techniqueused is Probability Sampling using simple random sampling, the tool used for data collectionis a questionnaire then analyzed using the Spearman Rank test proceed with the Z score.The results of statistical tests with Spearman rank based on Rank Spearmen statisticaltest obtained the value of P-Value (0.016) <? (0.05) followed by Z score (0.112) whichmeans that there is an effect DMPA contraseption usage time on decreased libido in womenof childbearing age .It should be noted that the use of hormonal contraseption especially for DMPA so as not todisturb the body system. At least if you have taken 2 years, you are advised to use nonhormonal contraception.